Bulk and surface electron dynamics in a p-type topological insulator SnSb2Te4 - Niesner, Daniel; Otto, Sebastian; Hermann, Volker; Fauster, Thomas; Menshchikova, T. V.; Eremeev, S. V.; Aliev, Z. S.; Amiraslanov, I. R.; Babanly, M. B.; Echenique, P. M.; Chulkov, E. V. (Physical Review B, 2014)
Time-resolved two-photon photoemission was used to study the electronic structure and dynamics at the surface of SnSb2Te4, a p-type topological insulator. The Dirac point is found 0.32 +/- 0.03 eV above the Fermi level. Electrons from the conduction band minimum are scattered on a time scale of 43 +/- 4 fs to the Dirac cone. From there they decay to the partly depleted valence band with a time constant of 78 +/- 5 fs. The significant interaction of the Dirac states with bulk bands is attributed to their bulk penetration depth of similar to 3 nm as found from density functional theory calculations.

Complex manifold of Rashba and image-potential states on Bi/Ag(111) - Rosenzweig, Philipp; Otto, Sebastian; Fauster, Thomas (Physical Review B, 2018)
Angle-resolved, mono- and bichromatic two-photon photoemission was used to study the electronic structure at the surface of the giant Rashba system Bi/Ag(111). The photoemission intensity maps are exceptionally rich in structure due to a large manifold of initial and intermediate states that allow for various resonant interband transitions. Using different photon energies, we succeeded in disentangling the complex experimental data. Close to the Fermi level the unoccupied, Rashba-split p(x)p(y) (m(j) = 1/2) surface state can be identified with a Rashba parameter of 3.0 +/- 0.2 eV A and a lifetime of 26 +/- 5 fs. At higher energies the spin-split p(x)p(y) (m(j) = 3/2) and p(z) bands as well as the first three members of a series of image-potential resonances were observed. Circular dichroism was used to gain information on the spin structure of both the initial and intermediate states and to corroborate the assignment to Rashba bands.

Electron dynamics of unoccupied states in topological insulators - Niesner, Daniel; Otto, Sebastian; Fauster, Thomas; Chulkov, E. V.; Eremeev, S. V.; Tereshchenko, O. E.; Kokh, K. A. (Journal of Electron Spectroscopy and Related Phenomena, 2014)
The topological insulators Bi2Se3 and Bi2Te2Se have been shown to possess unoccupied topological surface states at the center of the surface Brillouin zone at energies around 1.3 eV above the Fermi level. Using time-resolved two-photon photoemission we study the electron dynamics of the unoccupied topological surface states, image-potential states and conduction bands on these surfaces. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Topological insulators; Surface states; Image-potential states; Two-photon photoemission; Electron dynamics

Mapping the band structure of GeSbTe phase change alloys around the Fermi level - Kellner, Jens; Bihlmayer, Gustav; Liebmann, Marcus; Otto, Sebastian; Pauly, Christian; Boschker, Jos Emiel; Bragaglia, Valeria; Cecchi, Stefano; Wang, Rui Ning; Deringer, Volker L.; Küppers, Philipp; Bhaskar, Priyamvada; et al. (Communications Physics, 2018)

Origin of spin-polarized photocurrents in the topological surface states of Bi2Se3 - Ketterl, A. S.; Otto, Sebastian; Bastian, M.; Andres, B.; Gahl, C.; Minar, J.; Ebert, H.; Braun, J.; Tereshchenko, O. E.; Kokh, K. A.; Fauster, Thomas; Weinelt, M. (Physical Review B, 2018)
For the generation of spin-polarized photocurrents in topological insulators, a coupling between photon angular momentum and electron spin is often assumed. Such a coupling seems to be supported by dichroism reported in E(k(y))-intensity maps in photoemission. We show in three dimensional two-photon photoemission and one-step photoemission calculations that the circular dichroism is in fact threefold in E(k(x), k(y)) maps although it may appear antisymmetric in E(k(y)). The threefold symmetry is inconsistent with the previously assumed coupling between photon momentum and electron's chiral spin via the orbital momentum. Instead it reflects the surface point group. The only antisymmetric patterns appear in the energy range in which surface and bulk states hybridize. In general, a threefold-symmetric dichroic signal does not support unidirectional photocurrents. Nevertheless, the residual asymmetry of up to 3.5% in our photoemission spectra is compatible with previously observed helicity-dependent photocurrents.

Strong and Weak 3D Topological Insulators Probed by Surface Science Methods - Morgenstern, Markus; Pauly, Christian; Kellner, Jens; Liebmann, Marcus; Pratzer, Marco; Bihlmayer, Gustav; Eschbach, Markus; Plucinski, Lukacz; Otto, Sebastian; Rasche, Bertold; Ruck, Michael; Richter, Manuel; et al. (physica status solidi (b), 2020)
The contributions of surface science methods to discover and improve 3D topological insulator materials are reviewed herein, illustrated with examples from the authors’ own work. In particular, it is demonstrated that spin-polarized angular-resolved photoelectron spectroscopy is instrumental to evidence the spin-helical surface Dirac cone, to tune its Dirac point energy toward the Fermi level, and to discover novel types of topological insulators such as dual ones or switchable ones in phase change materials. Moreover, procedures are introduced to spatially map potential fluctuations by scanning tunneling spectroscopy and to identify topological edge states in weak topological insulators.
CRIS-Team Scopus Importer:2020-05-22
Keywords: angular-resolved photoelectron spectroscopy; scanning tunneling spectroscopy; spin-polarized topological insulators

Two-photon photoemission from CoO layers on Ir(1 0 0) - Otto, Sebastian; Fauster, Thomas (Journal of Physics: Condensed Matter, 2016)
Two-photon photoelectron spectroscopy is used to study the unoccupied electronic states of cobalt oxide layers on Ir(1 0 0). For thicker layers of (1 0 0) orientation the conduction band minimum is found 2 eV above the Fermi level. Layers with (1 1 1) orientation and thickness ⩽ 4 bilayers show a peak around 3.4 eV energy and no evidence for the conduction band minimum. This is attributed to the metallic character of thin CoO(1 1 1) layers.
Keywords: cobalt oxide; electronic states; work function; two-photon photoemission